Gender differences in the transition to adulthood in France: Is there convergence over the recent period? - Maria Winkler-Dworak; Laurent Toulemon (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2007)
Numerous studies have shown that educational attainment and labour force status have a strong impact on the timing of family formation for both men and women. The effects of educational level, enrolment in an educational setting and employment seem to be different for men and women. The aim of this paper is to investigate how gender-specific differences in family formation changed over time, particularly, whether these differences have vanished in recent years. We use a large-scale survey (more than 240,000 men and women born after 1940) conducted within the French 1999 census and apply event history techniques. The sample size allows us to test our hypotheses with more sophisticated models that cover several interactions. Our data fully support the convergence hypothesis for men and women with regard to the effects caused by educational attainment and the working status (working/not working). However, it is only partly relevant for the effects of their enrolment status on entry into first union and parenthood. The impact of work experience on first union and first parenthood has developed similarly over time for both men and women.
Keywords: 300; Transition to adulthood; family formation; event history analysis; France; gender; education; Familienplanung; Geschlechterdiskriminierung; Kinderbetreuung; Bildungsniveau; Familienökonomik; Schätzung; Frankreich